The Impact of Political Regime and Institutions on Government Size in Middle-Income Countries (The Pakistan Development Review, 2020)
This study analyses the impact of political regimes and institutions on government size while controlling for socio-economic factors for a group of 56 middle income countries over the period 1986-2014. The empirical analysis shows that the institutional quality index has a negative impact on government size. Furthermore, institutions have a positive impact on “productive” government spending, while having a negative impact on “unproductive” government spending. The analysis also shows that institutional democracy, political regime and stability of political system are the key political determinants of government size. A stable democratic system backed by well-defined institutions could help to manage government size. It ensures transparency and political contestability which leads to control over the use of public resources. The analysis further shows that the GDP per capita has a positive and significant impact on government size at all stages of development. It implies that there is a natural growth of government size due to economic development. This analysis provides useful insights for policy makers to manage government size. A stable political system supported by good quality institutions is a prerequisite to managing scarce public resources. JEL Classification: E13, O43, O47 Keywords: Political Regime, Institutions, Government Size, Middle Income Countries